2006
DOI: 10.1111/j.1600-079x.2006.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoperiod on the fish innate immune system: a link between fish pineal gland and the immune system

Abstract: The pineal gland via its secretory product, melatonin, influences the light-dark rhythm in most vertebrates including fish. Apart from the information concerning this circadian rhythm, the interrelation of the melatonin with other physiological processes has not been considered in fish. Thus, we evaluated the changes in the humoral innate immune system of seabream (Sparus aurata L.) and sea bass (Dicentrarchus labrax L.) specimens exposed to a constant light-dark photoperiod (12 hr L:12 hr D). Serum was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 58 publications
2
32
1
Order By: Relevance
“…The several clock genes identified may have immunological implications inAtlantic cod because they were highly expressed in immune-related organs and tissues, such as blood, liver, mid-intestine, gills, kidney, spleen and skin. In fact, it has been shown that the immune response in fish is regulated in a daily or seasonal pattern, and is affected by photoperiod conditions [40], [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…The several clock genes identified may have immunological implications inAtlantic cod because they were highly expressed in immune-related organs and tissues, such as blood, liver, mid-intestine, gills, kidney, spleen and skin. In fact, it has been shown that the immune response in fish is regulated in a daily or seasonal pattern, and is affected by photoperiod conditions [40], [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…During the winter months (when the daily dark photoperiod is long), melatonin is produced for a greater length of time relative to the shorter dark photoperiod of summer days in vertebrates [25]. These light-dark rhythms and the consequential changes in the level of melatonin in serum also influence many processes in fish such as sedation, skin pigmentation, oxygen consumption, osmoregulation, thermoregulation, food intake, shoaling behavior, and, as more recently described, immunity [7,8,32,3641]. In addition to light, melatonin production in fish is also affected by water temperature.…”
Section: Melatonin and Biological Rhythms In Fishmentioning
confidence: 99%
“…In addition to light, melatonin production in fish is also affected by water temperature. Higher levels of melatonin have been reported in fish maintained at a high temperature than in the same fish species maintained at lower temperatures [32]. Therefore, the immune response seems to be altered in daily/yearly cycles, and these changes appear to be related to water temperature.…”
Section: Melatonin and Biological Rhythms In Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar daily rhythms in chemotaxis and neutrophil migration have been described in human, mice and cows [7–9]. Diurnal rhythms in innate immune functions have been described in fishes, gilthead seabream and sea bass [44]. Both, the time of exposure of immunocompetent cells to an antigen [45,46] and the response to challenge of the immunized organism after the introduction of the antigen [45–49] show circadian variations in human subjects and animals.…”
Section: Resultsmentioning
confidence: 67%